Growth optimization of Saccharomyces cerevisiae and Rhizopus oligosporus during fermentation to produce tempeh with high ?-glucan content - SAMSUL RIZAL; Murhadi Murhadi; Maria Erna Kustyawati; Udin Hasanudin (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rizal S, Murhadi, Kustyawati ME, Hasanudin U. 2020. Growth optimization of Saccharomyces cerevisiae and Rhizopus oligosporus during fermentation to produce tempeh with high ?-glucan content. Biodiversitas 21: 2667-2673. Saccharomyces cerevisiae grows and produces ?-glucan during fermentation in tempeh production. The content of ?-glucan in tempeh is influenced by the growth of S. cerevisiae throughout fermentation. The purpose of this study was to determine the effects of different types and concentrations of carbon sources on yeast growth, fungi growth, and ?-glucan content in tempeh inoculated using Rhizopus oligosporus and S. cerevisiae. This study used a Factorial Randomized Complete Block Design (RCBD) with two factors and three replications. The first factor was the types of carbon sources, tapioca and wheat flour; the second factor was the concentrations of carbon source, 0.0%, 2.5%, 5.0%, 7.5% and 10.0% (w/w). Tempeh produced was investigated for yeast number, fungi number, ?-glucan content, and pH value. The obtained data were tested using Tukey's Honestly Significance Difference (HSD) test. The results showed that the addition of various types and concentrations of carbon source significantly influenced the increase in yeast number, fungi number, ?-glucan content, and pH in tempeh. The growth of yeast, fungi, and ?-glucan content increased along with the increment of carbon source concentration. The amounts of yeast, fungi, and ?-glucans in tempeh added with tapioca were higher compared to tempeh with wheat flour. The addition of 10% tapioca produced the highest amount of yeast with 9.505 Log CFU/g and the highest ?-glucan content with 0.707% (w/w).